Influência do SNP T3801C CYP1A1 sobre os níveis de danos oxidativos no DNA de células da mucosa gástrica de pacientes infectados pelo H. Pylori - Sagawa, Cíntia Helena Duarte [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Helicobacter pylori (H. pylori) is a common gastric pathogen that has infected more than 50% of the population of the world and it has been associated with chronic gastritis, gastric ulcers, duodenal ulcer, and gastric cancer. Although, almost all infected people develop gastritis, there is a variety of clinical outcomes, and only a minority (<1%) of infected individuals develop gastric cancer. There are evidences which suggest that the chronic inflammatory reaction caused by the bacterial infection may be involved in the production of reactive oxygen species or reactive nitrogen species. It may lead to DNA damage, which together with the cellular response could lead to gene mutations, chromosomal aberrations characterizing genomic instability that may represent the early step in gastric carcinogenesis. The extent and severity of gastric mucosal inflammation, as well as the clinical outcome of the infection, depend on a number of factors, including the host genetic susceptibility such SNP T3801 CYP1A1, immune response, age at which the infection was acquired, environmental factors, especially dietary and bacterial virulence factors. Due to the risk of developing gastric cancer in humans infected by H. pylori, we used the Comet Assay to investigate the influence of the SNP T3801C CYP1A1 on levels of oxidative DNA damage in gastric epithelial cells. The study was conducted with biopsies from the gastric antrum and corpus of 103 H. pylori-infected patients and 24 uninfected control patients. Genotype of SNP T3801C CYP1A1 was determined by PCR-RFLP and DNA damage levels were measured in gastric mucosal cells from antrum and corpus by the Comet assay. Levels of DNA damage in gastric mucosa cells from antrum and corpus of H. pylori-infected patients with mild, moderate, severe gastritis, and gastric cancer were significantly higher compared to uninfected normal mucosa cells. However, levels... (Complete abstract click electronic access below)

O Helicobacter pylori (H.pylori) é um patógeno gástrico que infecta mais de 50% da população mundial e tem sido associado com gastrite crônica, úlcera gástrica, úlcera duodenal e câncer gástrico. Embora a maioria das pessoas infectadas desenvolva gastrite, há uma variedade de respostas clínicas, e apenas uma minoria (<1%) dos indivíduos infectados desenvolve câncer gástrico. Evidências sugerem que a reação inflamatória crônica causada pela infecção bacteriana pode estar envolvida na produção de espécies reativas de oxigênio ou espécies reativas de nitrogênio. Isso pode causar danos no DNA, que junto com a resposta celular poderia gerar mutações gênicas e aberrações cromossômicas, caracterizando instabilidade genômica que representaria um primeiro passo na carcinogênese gástrica. A extensão e a severidade da inflamação da mucosa gástrica, assim como a resposta clínica da infecção, dependem de vários fatores, incluindo a suscetibilidade genética como o SNP T3801C CYP1A1, resposta imune, idade que a infecção foi adquirida, fatores ambientais, especialmente a dieta e fatores de virulência bacteriana. Devido ao risco de desenvolvimento de câncer gástrico em humanos infectados pelo H. pylori, utilizamos o Ensaio Cometa para investigar a influência do SNP T3801C CYP1A1 sobre os níveis de danos oxidativos no DNA nas células epiteliais gástricas. O estudo foi conduzido a partir de biópsias do antro e corpo gástrico de 103 pacientes infectados H.pylori e 24 pacientes controles (não infectados). A genotipagem do SNP T3801C CYP1A1 foi determinada por PCR-RFLP e os níveis de danos no DNA em células da mucosa do antro e corpo gástricos pelo Ensaio Cometa. Os níveis de danos no DNA nas células epiteliais gástricas de pacientes infectados pelo H. pylori com gastrite leve, moderada e severa e câncer gástrico foram significativamente maior... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Genética; Helicobacter pylori - Efeito fisiológico; DNA